Modelling and Interpretation of Adsorption Isotherms - Nimibofa Ayawei; Augustus Newton Ebelegi; Donbebe Wankasi (Journal of Chemistry)
The need to design low-cost adsorbents for the detoxification of industrial effluents has been a growing concern for most environmental researchers. So modelling of experimental data from adsorption processes is a very important means of predicting the mechanisms of various adsorption systems. Therefore, this paper presents an overall review of the applications of adsorption isotherms, the use of linear regression analysis, nonlinear regression analysis, and error functions for optimum adsorption data analysis.